Strategi Pengelolaan Biaya Operasional pada Toko Malika - Telaumbanua, Justri Yani; Maria, Alleta Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article explores operational cost management strategies at Malika Store to enhance efficiency and profitability. The study focuses on the challenges of managing operational costs and their impact on financial performance. Data were collected through semi-structured interviews with the owner, manager, and employees, as well as direct observations of the store’s operations. Using a qualitative analysis approach, the findings show that inventory efficiency, supplier negotiation, and technology utilization significantly contribute to reducing costs and boosting profitability. Inventory efficiency minimizes waste while negotiating with suppliers helps reduce purchasing costs. Technology utilization, such as inventory management systems, also optimizes store operations. The study's findings are expected to be broadly applicable in the retail sector, providing practical guidance for business owners on managing operational costs more effectively to achieve better financial performance.